The Seismo‐Acoustics of Submarine Volcanic Eruptions. Issue 4 (26th April 2021) - Tepp, Gabrielle; Dziak, Robert P.
Abstract: Many of the world's volcanoes are hidden beneath the ocean's surface where eruptions are difficult to observe. However, seismo‐acoustic signals produced by these eruptions provide a useful means of identifying active submarine volcanism. A literature survey revealed reports of 119 seismo‐acoustically recorded submarine eruptions since 1939. Submarine eruptions have been recorded in all major tectonic settings, with a range of geochemistries, and at a variety of water depths, but the reports are dominated by eruptions in the Pacific and at only a few locations. Many of the reports offer little detail, with over half of the observations made from distances >500 km, and only about half were confirmed as eruptions by non‐seismo‐acoustic evidence. The reported seismo‐acoustic signals cover a wide variety of processes, including earthquakes, explosions, various types of tremor, signals related to lava extrusion, and landslides. Recorded signals can sometimes be difficult to classify or confidently associate with an eruption, although there has been progress in this regard. Real‐time monitoring of submarine eruptions has been on‐going for several decades on regional and global scales with growing interest and effort in local networks. Real‐time networks are complemented by short‐term instrument deployments that often give more detailed insights into the dynamics and processes of submarine eruptions. Thorough seismo‐acoustic monitoring and study has increased our understanding of submarine eruptions, especially of deep‐sea volcanoes and spreading centers. Despite this, there are still many outstanding questions that need to be addressed for submarine volcanoes to be as well understood and monitored as their terrestrial counterparts. Key Points: A literature survey found reports of 119 submarine volcanic eruptions recorded by seismic, hydroacoustic, or acoustic instruments since 1939 This review summarizes the current state of submarine eruption seismo‐acoustics based on the literature survey results Seismo‐acoustic monitoring and study has increased our understanding of submarine eruptions but many scientific opportunities remain